The Predictive value of serum glutathione S-transferase (GST-π), P-glycoprotein (PGP), P53, Ki-67 and breast cancer :Systematic review and meta-analysis: serum markers and breast cancer - zhang, nuan (Journal of Medical Biochemistry, 2025)
Objective: To evaluate the correlation between triple-negative breast cancer (TNBC) and drug-resistant protein expression, and to provide reference for improving the treatment of TNBC.Methods: The relevant literature was searched through PubMed, Web of Science, CNKI, WanFang data, along with VIP databases from 2010 to 2024. Literature screening together with data extraction were implemented by two researchers, and literature quality was evaluated. Meta-analysis was implemented on the extracted data by means of RevMan 5.3 software.Results: There were 7 literatures included, all of which were in English. Meta-analysis results revealed that, compared to non-TNBC, the expression rate of GST-π protein in TNBC was elevated [OR=3.41, 95% CI (2.21, 5.25), P
Keywords: serum glutathione S-transferase (GST-π), P-glycoprotein (PGP), P53, Ki-67,triple negative breast cancer; chemotherapy resistance; drug resistant protein; meta-analysis.